Dzulkifli Abdul Razak, Fourth Industrial Revolution: The Leadership Dilemma. Negri Sembilan: USIM Press, 2018. 56+x pp. ISBN 978-967-440-492-5 - Quayum, Mohammad Abdul (IIUM Press, International Islamic University Malaysia, 2018)
A review of Dzulkifli Abdul Razak's Fourth Industrial Revolution: The Leadership Dilemma which provides an analytical discussion of the book's content and highlights its merits and contribution to the subject. It investigates the author's contention on why espousing 4 IR may not be necessarily good for Malaysia.